Development of Morning and Night Facial Makeup Learning E-Modules in Facial Makeup Courses - Yulisvi, Shafa; Hidayah, Nurul; Puspa Arum, Aniesa (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to develop an e-module for Daily Makeup (Morning and Evening) as an additional learning resource for the Makeup course in the Makeup Education Study Program at Universitas Negeri Jakarta. Using the Research and Development (RD) 4D model (Define, Design, Develop, Disseminate), the e-module was designed interactively with text, images, and simple navigation through the Canva application, accessible digitally. Research instruments included validation questionnaires for material experts, media experts, language experts, and practicality assessments from students. Validation results showed that the e-module was deemed